Necesidad de garantizar el derecho al trabajo de las personas que se encuentran en situación de refugiados en el Ecuador - Montaño Rayo, Santiago (2014)
In Ecuador foreigners living in refugee situations by internal conflicts of those who request it, in which our country welcomes them, what comes to constitute a situation of humanity, question welcomed by the international community. But it happens that these people can not get a decent job, because among the requirements demanded by employers is to have work experience or have a professional or technical degree, but these people do not have it because they have fled their homes and can not attend their countries to request documents proving them work experience, making it impractical to hire them for activities they know and have experience. In this respect the labor law says nothing about the matter of hiring people who are in refugee situation, so do not hold the full enjoyment and exercise of rights, being necessary to determine mechanisms for refugees can be considered equal in situations of equality and rights. They are given jobs to people refugees does not mean you remove our citizens the right to work, but a small percentage is established that the employer can accommodate refugees in their companies, to thereby protect, respect the right to work of refugee claimants